The pixelated text: Reading the Bible within digital culture - Phillips, Peter (Theology, 2018)
This article looks at Bible engagement in a digital age, focusing both on multimedia engagement with the Bible through the ages and on the changes that new technologies bring to the reading process, and asking some questions about our use of different technologies for different tasks. The article opens up the new possibilities afforded to scholars through the digitization of manuscripts and libraries, but also looks at the limitations of digital Bibles in their current forms. What new areas of research do the digital humanities open up for us?